2020
DOI: 10.1001/jamasurg.2020.1133
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal Gastric Cancer–Associated Long Noncoding RNA1 as a Biomarker for Early Detection and Monitoring Progression of Gastric Cancer

Abstract: IMPORTANCE The gastric cancer (GC)-associated long noncoding RNA1 (lncRNA-GC1) plays an important role in gastric carcinogenesis. However, exosomal lncRNA-GC1 and its potential role in GC are poorly understood. OBJECTIVE To evaluate the diagnostic value of circulating exosomal lncRNA-GC1 for early detection and monitoring progression of GC. DESIGN, SETTING, AND PARTICIPANTS We performed a multiphase investigation of circulating exosomal lncRNA-GC1 for early detection of GC involving consecutive patients with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 25 publications
0
104
0
Order By: Relevance
“…Massive studies have elucidated that lncRNAs play important roles in the pathogenesis and progression of multiple cancers 10,21,23,26 . Currently, lncRNAs show great potential as targets and combined targeting of dysregulated lncRNAs may become a promising option for future cancer therapeutics 35,36 . Therefore, it is of great significance to enlarge the identification of lncRNAs and their underlying mechanisms, thereby facilitating the progress of lncRNA‐based treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Massive studies have elucidated that lncRNAs play important roles in the pathogenesis and progression of multiple cancers 10,21,23,26 . Currently, lncRNAs show great potential as targets and combined targeting of dysregulated lncRNAs may become a promising option for future cancer therapeutics 35,36 . Therefore, it is of great significance to enlarge the identification of lncRNAs and their underlying mechanisms, thereby facilitating the progress of lncRNA‐based treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the diagnostic potential of these EV biomarkers was higher than CEA or CA19.9. In a larger study by Guo et al [ 157 ], involving 826 individuals, lncRNA-GC1 was found to discriminate GC in early GC patients, in healthy individuals with or without H. Pylori infection, and individuals with pre-malignant gastric lesions (intestinal metaplasia and atrophic gastritis) ( Table 6 ). Although endoscopy is required for a conclusive diagnosis, it is conceivable to assume that the combination of standard biomarkers and EV-specific cargoes may be useful to better select patients requiring invasive diagnostic procedures.…”
Section: Cancers Of the Gastrointestinal Tractmentioning
confidence: 99%
“…For example, prostate-specific lncRNA prostate cancer antigen 3 (PCA3) levels have been suggested as a diagnostic biomarker of prostate cancer ( 98 ). Other lncRNAs used as biomarkers include circulating plasma H19 for gastric cancer ( 99 ), HULC in hepatocellular carcinoma ( 100 ), circulating lncRNA in SNHG11 colorectal cancer ( 101 ), circulating exosomal lncRNA-GC1 in gastric cancer ( 102 ), and HOTAIR in various cancers, including breast, colorectal, liver, gastric, lung, and thyroid ( 103 107 ).…”
Section: Therapeutic Use Of Lncrnas In Diseasesmentioning
confidence: 99%